Single-center results from the first 100 robotic ureteral reimplantation in children: analysis of learning curve effects - Mattioli, G.; Brenco, G.; Fanti, F.; Rotondi, G.; Verrina, E.; Piaggio, G.; Damasio, M. B.; Carlucci, M.; Fiorenza, V. (Frontiers in Surgery, 2025)
IntroductionRobot-assisted laparoscopic ureteral reimplantation (RALUR) is increasingly utilized in pediatric urology, yet outcomes vary widely and the learning curve remains under-investigated. This study aims to evaluate perioperative outcomes and learning curve progression during the first 100 pediatric RALUR procedures performed by a single surgeon.MethodsA prospective, single-center study was conducted on 100 RALUR procedures in 96 pediatric patients between May 2020 and May 2025. The cohort was divided into two groups (first 50 cases vs. second 50) to assess the impact of surgical experience on outcomes. Surgical techniques included both dismembered (D-RALUR) and non-dismembered (ND-RALUR) approaches based on anatomical indications. Clinical data, complications and outcomes were recorded.ResultsSuccess rates improved significantly from 66% in Group A to 84% in Group B (p = 0.04). Postoperative vesicoureteral reflux occurred in 28% in Group A vs. 10% in Group B (p = 0.02). Complication rates decreased from 18% to 12%, with no conversions to open surgery in either group. The need for opioid analgesia was significantly lower in Group B (4% vs. 14%, p = 0.04). Our analysis showed a decreasing trend in both failure and complication rates, reflecting progressive improvement in surgical proficiency. RALUR was safely applied to increasingly complex cases, including redo surgeries and anatomical anomalies.DiscussionRALUR is a safe and effective technique for ureteral reimplantation in children, even in complex or redo cases. Surgical outcomes improved with experience, underscoring a manageable learning curve. The implementation of standardized techniques and increased surgeon expertise contributed to enhanced success rates and reduced morbidity. These findings support early integration of robotic training in pediatric urology and the broader adoption of RALUR in centers with appropriate expertise.